2000
DOI: 10.4269/ajtmh.2000.63.192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic variants of hepatitis GB-C/HG and TT viruses in Gabon, equatorial Africa.

Abstract: Abstract. The distribution of Hepatitis GB-C/HG (GB-C/HG) and TT viruses (TTV) infections was investigated in selected populations from Gabon using Polymerase Chain Reaction (PCR) and Enzyme Linked Immunosorbent Assay (ELISA) for anti-Envelop 2 (anti-E2) GBV-C/HGV antibodies. Among pregnant women, 29 of 229 (12.6%) were Hepatitis GB virus-C and Hepatitis G virus (GBV-C/ HGV) RNA positive (ϩ) and 32 of 81 (39.5%) anti-E2 ϩ versus 8 of 39 (20.5%) TTV DNA ϩ. Among sickle cell anemia patients, 9.7% (3/31) were GBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
11
1
Order By: Relevance
“…In healthy Kuwaitian, Jordanian and Tunisian blood donors the HGV prevalence of 24.6; 9.8% and 5.3%, have been reported, respectively 20,21. In central Africa, HGV prevalence of 10.3% and 12.6% was also found among pregnant women 22,23…”
Section: Discussionmentioning
confidence: 99%
“…In healthy Kuwaitian, Jordanian and Tunisian blood donors the HGV prevalence of 24.6; 9.8% and 5.3%, have been reported, respectively 20,21. In central Africa, HGV prevalence of 10.3% and 12.6% was also found among pregnant women 22,23…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of GBV-C infection in the general population is higher than that of other bloodborne viruses, such as human immunodeficiency virus (HIV) and hepatitis C virus in western industrialized countries and varies globally, as does GBV-C genotype. Among antenatal populations, the prevalence of GBV-C RNA varies from 1%-2% in East Asia [1,2] to 5%-7% in Europe, Australia, and Southeast Asia [3][4][5][6] and 10%-13% in Africa [7,8]. GBV-C infection is also more prevalent in HIV-infected persons and others with risk factors for bloodborne infections [9] and can be transmitted parenterally, sexually, and vertically [10].…”
mentioning
confidence: 97%
“…At‐risk populations such as patients with liver disease, hemodialysis patients, or transplant patients have been evaluated in several studies. Tuveri et al reported that 10.7% of hepatocellular carcinoma cases in Gabon were HPgV‐positive . In South Africa, 2 studies have reported HPgV prevalence rates of 23.8% to 24.3% in hemodialysis patients, 41.2% in renal transplant patients, 23.5% in hemophiliacs, and 12.2% in patients with chronic liver disease .…”
Section: Resultsmentioning
confidence: 99%